2016
DOI: 10.1097/pcc.0000000000000659
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Overload Is Associated With Higher Mortality and Morbidity in Pediatric Patients Undergoing Cardiac Surgery*

Abstract: Fluid overload in the early postoperative period was associated with higher mortality and morbidity. Risk factors for fluid overload include underlying kidney dysfunction, hemodynamic instability, and higher blood loss on the day of the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 29 publications
8
69
0
4
Order By: Relevance
“…Recent evidence suggests that fluid overload after cardiac surgery leads to prolonged mechanical ventilation [46, 47]. In this study, subjects without AKI had LOS that were correlated with factors that suggested an increased need for cardiac support in the immediate postoperative period such as longer CPB duration, higher surgical complexity, higher VIS scores, and need for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 75%
“…Recent evidence suggests that fluid overload after cardiac surgery leads to prolonged mechanical ventilation [46, 47]. In this study, subjects without AKI had LOS that were correlated with factors that suggested an increased need for cardiac support in the immediate postoperative period such as longer CPB duration, higher surgical complexity, higher VIS scores, and need for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 75%
“…Practice varies within PICU's with reductions from 25–50% from the Holliday‐Segar equation which still remains the standard method for calculating maintenance fluid requirements in paediatrics . There is growing evidence of the adverse impact of early fluid overload administration on clinical outcomes in paediatric critically care patients . In our work, we tested all our concentrations in clinical scenarios to confirm that the concentrations used would not exceed our fluid regime.…”
Section: Discussionmentioning
confidence: 83%
“…3 For non-responders, the unnecessary intravascular volume expansion might cause interstitial and tissue edema with compromised microvascular perfusion and decreased oxygen delivery that may be responsible for an increase in morbidity in critically ill children. 4,5 Fluid goal-directed therapy was developed in adults but has seen slow adoption and restricted applications in the pediatric setting based on old publications. 6 This is partly due to children's physiological characteristics, related to thoracopulmonary and vascular compliance, that impede the reliability of predictive markers of fluid responsiveness.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…However, in pediatric patients, the response rate to blinded fluid challenge ranged from 45% to 69% . For non‐responders, the unnecessary intravascular volume expansion might cause interstitial and tissue edema with compromised microvascular perfusion and decreased oxygen delivery that may be responsible for an increase in morbidity in critically ill children …”
Section: Introductionmentioning
confidence: 99%